Bloques de tierra comprimida estabilizado con ceniza de fibra de bagazo de caña de azúcar y cal, comparado con un cementante artificial - Paqui Zhunaula, Olger Geovanny (2018)
Abstract:This investigation contributes to the study of the mechanical characteristics of stabilized compressed earth blocks (CEBs) with the purpose of optimizing its mechanical behavior for construction uses. An experiment was performed by adding to CEBs a pozzolanic cementitious materials made of lime and sugarcane fiber ash mixed in different proportions. The properties of this improved CEB were then compared with the properties of a BTC that was stabilized with Portland cement, an artificial cementing material. The comparison involved tests of compression, flexion, abrasion and erosion. From these tests and comparisons, the study determines the most adequate stabilizing mixture to be added in CEBs that are used in construction.